The influence of resilience and sustainability perception on airport brand promotion and desire to reuse of airport services: the case of Iran airports - Pishdar, Mahsa; Ghasemzadeh, Fatemeh; Maskeliūnaitė, Lijana; Bražiūnas, Justas (Transport, 2019)
Sustainability and resilience are important in social, economic and environmental aspects. However, inspections show that in developing countries like Iran, sustainability and resilience strategies lose their significance when economic problems and high workload come to matter. This research tries to determine what factors encourage managers to consider airport sustainability in long-term and different situations. Such investigations are essential for a developing country like Iran, which has 54 airports under a central management system, which can help deploying selected strategies. Results of this study show that if passengers perceive the sustainability activities and ethical cores of an airport, they consider it more prestigious and become willing to reuse airport services for their future travels. They also turn out as evangelists and changes of the way people travel becomes visible on a wider scale. This can help managers to understand recent travel behaviour of airport passengers and enhance the airports’ performance considering different aspects equally, which are profitable for airport system, public and environment as a whole.